Pengembangan Permainan Ular Tangga untuk Meningkatkan Kemampuan Berhitung Permulaan Anak Usia 5-6 Tahun - Aulia Rizkiana; Fahruddin; Baik Nilawati Astini; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2021)
Numeracy skills of children aged 5-6 years in Tanak Malit Utara Masbagik District are still low due to the lack of use of media and game tools in the learning process, and the methods used by the teacher in teaching are still using the lecture method. The purpose of this study was to find out how to develop a game of snakes and ladders to improve the beginning counting skills of children aged 5-6 years in the Tanak Malit Utara of Masbagik Sub-district in 2020. This type of research is development research with reference to the opinion of Borg & Gall. The research subjects were children aged 5-6 years in Tanak Malit Utara Masbagik Sub-district. Methods of data collection in this study using the method of observation, documentation, and FGD (Focus Group Discussion). The data analysis technique in this research was descriptive qualitative. The research used three stages of development with six meetings. Each stage an increase occurs by modifying the tools and materials, the steps of the game, and the rules of the game. The results obtained at the development stage I (meeting I) obtained a percentage value of (41,6%). There was an increase in development stage III (meeting VI or last) was (91,6%).